Realignment of Flight Information Region Agreement Between Indonesia and Singapore 2022: Unraveling Sovereignty and Ratification Issues for Indonesia - Muhammad, Naufal Faiz; Latipulhayat, Atip; Pratama, Garry Gumelar (Faculty of Law, Universitas Padjadjaran, 2024)
Flight Information Region (FIR) is an essential part of the aviation sector, providing air navigation and alerting services crucial for ensuring flight safety. States may delegate the management of FIR services to other nations for various reasons, primarily centered on aviation safety. However, such delegation requires careful consideration due to its potential impact on a state’s airspace sovereignty. This study focuses on the most recent FIR delegation involving the realignment of FIR over the Riau and Natuna Islands between Indonesia and Singapore in 2022. According to the signed agreement, Indonesia is obligated to delegate the management of specific areas of the Natuna FIR above its territory to Singapore. While this delegation poses potential challenges related to Indonesia's national security and economic interests, additional issues arise from the legal instrument chosen by the Indonesian government to ratify the agreement. The objective of this research is to analyze the sovereignty and ratification issues for Indonesia arising from the signing of the Indonesia-Singapore FIR Agreement 2022. The study utilizes normative legal analysis with a juridical approach. The findings indicate that the delegation of the Natuna FIR to Singapore has restricted Indonesia's right to exercise sovereignty over its airspace. Furthermore, the study concludes that Indonesia’s instrument of ratification for the Indonesia-Singapore FIR Agreement 2022 is inconsistent with Indonesian law and practice. This research contributes to understanding the legal implications of FIR management delegation, emphasizing the importance of aligning such agreements with domestic legal frameworks.DOI: https://doi.org/10.22304/pjih.v11n1.a1